QR Code As the Delivery of Information to Universities - Sudarto, Ferry; Martono, Dedi; Hartatik, Rika Ayu Desi (Aptisi Transactions On Technopreneurship (ATT), 2019)
Wall or magazine magazines are a means of delivering information on Raharja College campus. In the delivery of information, the magazine has been widely spread in several applications of Raharja College, iRan and GreenDoc. However, this is still not optimal because the method used is still using paper. And also the lack of awareness of students will read the information on the magazine. QR codes are a type of two-dimensional matrix code or bar code developed by Denso Wave in 1994. With that, the form of information is reduced to a QR code that can store detailed information displayed on a monitor screen available at several strategic corners of the campus and scan the code on the main page of the online magazine website. The method used is the waterfall method, observation, and literature study and journal references as supporting in writing. This research was designed to make it easier to access information and attract reading interest to students of Raharja College.